1999
DOI: 10.1136/vr.145.8.218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lairage time on body temperature and glycogen reserves of broiler chickens held in transport modules

Abstract: Commercial broiler chickens killed in two processing plants, one in the south of England, the other in Scotland, in two seasons (winter and summer) and on two occasions in each season, were used to investigate the effects of killing the birds immediately on arrival or holding them in lairage for one, two, three or four hours. The two most important consequences of holding the birds in lairage were that their body temperature increased and their liver glycogen was depleted. The body temperature increased with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 10 publications
1
24
2
5
Order By: Relevance
“…Poor welfare during hen and rooster transport may result in an increase in the number of birds dead or injured on arrival at the slaughterhouse (Knowles and Broom, 1990), change in body temperature (Warriss et al, 1999), alterations in bio- (Savenije et al, 2002;Nijdam et al, 2005), or haematological indices of stress loads (Mitchell et al, 1992). The mean DOA percentage of hens and roosters found in our study was 0.925%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor welfare during hen and rooster transport may result in an increase in the number of birds dead or injured on arrival at the slaughterhouse (Knowles and Broom, 1990), change in body temperature (Warriss et al, 1999), alterations in bio- (Savenije et al, 2002;Nijdam et al, 2005), or haematological indices of stress loads (Mitchell et al, 1992). The mean DOA percentage of hens and roosters found in our study was 0.925%.…”
Section: Discussionmentioning
confidence: 99%
“…Warriss et al (1999) studied the effects of lairage time on body temperature and glycogen reserves of broiler chickens held in transport modules. They found that the body temperature of broilers increased with the time they were held in lairage.…”
mentioning
confidence: 99%
“…During fasting, birds have to mobilise their body energy reserves. If the total duration of pre-loading fasting, loading, transport, and lairage is too long, body energy reserves can become exhausted, thereby increasing the risk of hypothermia and death (Warriss et al 1999;Dadgar et al 2011Dadgar et al , 2012Caffrey et al 2017). During fasting, energy required for metabolism is obtained initially from carbohydrates and then by catabolism of fat and proteins into glucose (Riesenfeld et al 1981).…”
Section: Duration Without Feed Before Loading and Effects Of Fastingmentioning
confidence: 99%
“…If in a holding barn, the birds remain in crates on the trailer the, provision of adequate ventilation to all of the birds in the load can be challenging. The temperature within the crates can rise above the external temperature and cause increases in the rectal temperature of the birds (Hunter et al 1998;Warriss et al 1999). In warm conditions, an evaporative cooling system in addition to fan ventilation can be beneficial in reducing mortality in holding barns (Shackelford et al 1984).…”
Section: Lairage/holding Barn Conditionsmentioning
confidence: 99%
“…La glucosa se une al transportador, cambia su conformación y transporta la glucosa para ser transportada; en el hígado de los pollos de engorde se han reportado genes de las isoformas de transportadores de glucosa (GLUT 1 y 2); sin embargo, las concentraciones de proteína GLUT 1 son indetectables en el hígado de los pollos que sugieren que esto puede no ser un transportador importante para esta ave (15). El hígado aviar aporta de manera significativa a la producción de las cantidades circulantes de glucosa y es sensible a la disminución de la ingesta de alimentos, de tal manera que en un ayuno de 6 a 24 horas se disminuyen las concentraciones de glucóge-no hepático y aumenta la gluconeogénesis (16,17). Para el caso del sistema cotransporte de glucosa acoplado al sodio, estos se encuentran ubicados en el epitelio intestinal y en el epitelio de los túbulos contorneados proximal y distal.…”
Section: Introductionunclassified